FUNCTIONAL RESPONSE- A FUNCTION OF PREDATOR AND PREY SPECIES - ABAS SHAH, MOHD; ALI KHAN, AKHTAR (The Bioscan, 2013)
The functional response types and parameters of 4th instar larvae, adult females and males of coccinellid predators, Adalia tetraspilota (Hope) and Hippodamia variegata (Goeze) were evaluated at five different densities of Aphis pomi De Geer, Brevicoryne brassicae (Linnaeus) and Aphis craccivora Koch in order to understand the effect of predator species and stage, and prey species on functional response and to understand their role for the aphids’ biological control. Experiments were carried out in petri dishes at 25±2oC and 65±5% R.H. and 14L: 10D photoperiod in a controlled environment room. All tested stages exhibited a Type II response. The attack rate (a) and handling time (Th) coefficients differed for various growth stages of each predator and for the three prey species tested. So did the parameter values for the two predators indicating that various predatory stages of a predator have different abilities to respond to increasing prey densities, so do the various predators for a particular prey species and a particular predator towards various prey species. Attack rate coefficients didn’t differ as much as the handling time, thus re-establishing the fact that handling time is a good indicator of the effectiveness of a predator